Distinct Disease Severity Between Children and Older Adults With Coronavirus Disease 2019 (COVID-19): Impacts of ACE2 Expression, Distribution, and Lung Progenitor Cells. (2nd January 2021) - Zhang, Zhao; Guo, Liyan; Huang, Li; Zhang, Che; Luo, Ruibang; Zeng, Liang; Liang, Huiying; Li, Qiuhui; Lu, Xiaoxia; Wang, Xianfeng; Ma, Chui Yan; Shao, Jianbo; et al.
Abstract: Background: Children and older adults with coronavirus disease 2019 (COVID-19) display a distinct spectrum of disease severity yet the risk factors aren't well understood. We sought to examine the expression pattern of angiotensin-converting enzyme 2 (ACE2), the cell-entry receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and the role of lung progenitor cells in children and older patients. Methods: We retrospectively analyzed clinical features in a cohort of 299 patients with COVID-19. The expression and distribution of ACE2 and lung progenitor cells were systematically examined using a combination of public single-cell RNA-seq data sets, lung biopsies, and ex vivo infection of lung tissues with SARS-CoV-2 pseudovirus in children and older adults. We also followed up patients who had recovered from COVID-19. Results: Compared with children, older patients (>50 years.) were more likely to develop into serious pneumonia with reduced lymphocytes and aberrant inflammatory response ( P = .001). The expression level of ACE2 and lung progenitor cell markers were generally decreased in older patients. Notably, ACE2 positive cells were mainly distributed in the alveolar region, including SFTPC positive cells, but rarely in airway regions in the older adults ( P < .01). The follow-up of discharged patients revealed a prolonged recovery from pneumonia in the older ( P < .025). Conclusions: Compared to children, ACE2 positive cells are generally decreased in older adults and mainly presented in the lower pulmonary tract. The lung progenitor cells are also decreased. These risk factors may impact disease severity and recovery from pneumonia caused by SARS-Cov-2 infection in older patients. Abstract : Compared to children, ACE2 positive cells in older adults are generally reduced and mainly distributed in lower pulmonary tract. Lung progenitor cells are also decreased. These risks may impact disease severity and recovery from pneumonia in older patients with COVID-19.